Temperature-Dependent Phase Transition Studies Of Multicomponent Crystals Of Hexamethylenetetramine And Isonicotinamide - Chia, Tze Shyang (2018)
In this research, thirty-one multi-component crystals of hexamethylenetetramine and isonicotinamide were successfully prepared and seven of them undergo temperature-dependent phase transitions, which were investigated by using variable-temperature single-crystal X-ray diffraction analysis. These seven multi-component crystals are hexamethylenetetramine‒2-methylbenzoic acid (1/2) (monoclinic P21/c ↔ orthorhombic Pccn, Tc = 164.5 (5) K), hexamethylenetetramine‒benzoic acid (1/2) (monoclinic Pn ↔ orthorhombic Fmm2, Tc = 257.5 (5) K), hexamethylenetetramine‒4-methylbenzoic acid (1/2) (monoclinic P21/n ↔ orthorhombic Cmcm, Tc = 265.5 (5) K), hexamethylenetetramine‒succinic acid (1/1) (monoclinic P21/n ↔ monoclinic P21/c, Tc = 219 (1) K).